2020
DOI: 10.7150/ijms.39667
|View full text |Cite
|
Sign up to set email alerts
|

Plasma Exosome-derived MicroRNAs as Novel Biomarkers of Traumatic Brain Injury in Rats

Abstract: Traumatic brain injury (TBI) is a widespread central nervous system (CNS) condition and a leading cause of death, disability, and long-term disability including seizures and emotional and behavioral issues. To date, applicable diagnostic biomarkers have not been elucidated. MicroRNAs (miRNAs) are enriched and stable in exosomes in plasma. Therefore, we speculated that miRNAs in plasma exosomes might serve as novel biomarkers for TBI diagnosis and are also involved in the pathogenesis of TBI. In this study, we … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(19 citation statements)
references
References 65 publications
4
15
0
Order By: Relevance
“…Importantly, its level in normal plasma is very low, as indicated by a low copy number in naïve rats and also in the human controls in our study. Similar to our observation, another recent study identified increased miR-9a-3p levels in plasma exosomes of rats with weight-drop–induced TBI compared with sham-operated controls [ 55 ]. Elevated serum miR-9 levels were also reported in a group of American-style football players with at least six years of playing experience and 41% with previously reported concussion, in comparison with nonathlete controls [ 24 ].…”
Section: Discussionsupporting
confidence: 91%
“…Importantly, its level in normal plasma is very low, as indicated by a low copy number in naïve rats and also in the human controls in our study. Similar to our observation, another recent study identified increased miR-9a-3p levels in plasma exosomes of rats with weight-drop–induced TBI compared with sham-operated controls [ 55 ]. Elevated serum miR-9 levels were also reported in a group of American-style football players with at least six years of playing experience and 41% with previously reported concussion, in comparison with nonathlete controls [ 24 ].…”
Section: Discussionsupporting
confidence: 91%
“…In rodent TBI model, specific EVs miRNA expression pattern (significantly increased miR-21, miR-146, miR-7a, and miR-7b; decreased miR-212) indicates the presence of an enhancement loop among neuroinflammation and EVs [ 71 ]. In another study, around 50 exosomal miRNAs were described to be altered after TBI (31 up-regulated and 19 down-regulated) [ 72 ].…”
Section: Evs In Injury and Traumamentioning
confidence: 99%
“…In recent years, increasing evidence has indicated that miRNAs play an important role in the pathological process after TBI [29][30][31] . miRNAs have been found to be able to freely pass through the BBB to the peripheral blood via exosomes, providing a basis for miRNA as a biomarker for brain function recovery after TBI [32][33][34] . Therefore, clarifying the role of miRNAs after TBI may be helpful for formulating treatment strategies in the future.…”
Section: Discussionmentioning
confidence: 99%